Total Binocular Blindness Resulting from an Untreated Seizure: A Case Report - Shushtarian, Seyed Mohammad Masoud; Eslami Vaghar , Mohammad; Pour Mazar , Reza; Shojaei, Ahmad (Journal of Ophthalmic and Optometric Sciences, 2024)
Cortical blindness is a rare but serious complication of seizure disorders, typically associated with occipital lobe involvement. We report a case of a 32-year-old female with a history of hydrocephalus who developed acute, irreversible bilateral blindness following an untreated generalized tonic-clonic seizure episode. Flash visual evoked potential (VEP) testing revealed cortical dysfunction, consistent with seizure-related occipital damage. This case suggests that untreated seizures may lead to permanent vision loss through cortical visual pathway disruption. It underscores the potential neurological risks of delayed seizure intervention and highlights the importance of timely management to mitigate such outcomes. The report is contextualized with a review of relevant literature on seizure-induced cortical visual impairment.